FAKTOR – FAKTOR YANG MEMPENGARUHI PENGELUARAN UNTUK BERMAIN JUDI ONLINE MAHASISWA UNIVERSITAS UDAYANA - -, Leonardo; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
This research aims to identify the factors influencing students' engagement in online gambling within the university environment, specifically at Udayana University. A survey method using a questionnaire was employed to collect data from 100 students across various study programs at Udayana University. The questionnaire was designed to assess factors such as money usage behavior, motives for engaging in online gambling, and situational factors that may influence online gambling behavior. The results of the data analysis indicate a significant relationship between situational factors and students' inclination towards online gambling. Moreover, the accessibility of online gambling platforms also plays a crucial role in increasing student participation in online gambling activities. These findings offer essential insights into understanding the factors driving students to engage in online gambling within academic settings. The implications of this research underscore the need for preventive approaches and appropriate interventions to mitigate the negative impacts and risks associated with online gambling behavior among students. Keywords : Online gambling, Students, Factors, Udayana University, Survey Klasifikasi JEL: L83, D80, D90